L-type calcium channels regulate filopodia stability and cancer cell invasion downstream of integrin signalling - Guillaume Jacquemet; Habib Baghirov; Maria Georgiadou; Harri Sihto; Emilia Peuhu; Pierre Cettour-Janet; Tao He; Merja Perälä; Pauliina Kronqvist; Heikki Joensuu; Johanna Ivaska (Nature Communications, 2016)
Filopodia have a prominent role in driving cancer cell invasion. Here, the authors show that L-type calcium channels are a druggable target regulating filopodia stability and maturation into focal adhesions in metastatic breast cancer cells.